2003
DOI: 10.1002/chin.200302067
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropyl Building Blocks for Organic Synthesis. Part 79. Mono‐ and Disubstituted N,N‐Dialkylcyclopropylamines from Dialkylformamides via Ligand‐Exchanged Titanium‐Alkene Complexes.

Abstract: Complexes. -Treatment of formamide with various alkenes (acyclic, cyclic, dienes, trienes) in the presence of Ti(O-iPr) 4 or Me-Ti(O-iPr) 3 offers a new and general approach to mono-and disubstituted cyclopropylamines. This reaction proceeds with excellent regioselectivity and in many cases with high stereoselectivity. -(DE MEIJERE*, A.; WILLIAMS, C. M.; KOURDIOUKOV, A.; SVIRIDOV, S. V.; CHAPLINSKI, V.; KORDES, M.; SAVCHENKO, A. I.; STRATMANN, C.; NOLTEMEYER, M.; Chem. Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The aza-Kulinkovich–de Meijere cyclopropanation of N- Boc-3-pyrroline ( 20 ) in particular had been described previously, with a reported 98:2 diastereoselectivity for the exo isomer in 76–90% yield . Reaction with N , N -dibenzylformamide ( 19 ) allows for orthogonal deprotection via hydrogenolysis to provide our desired 3- N- Boc- exo -6-amino-3-azabicyclo­[3.1.0]­hexane ( 5 ).…”
Section: Results and Discussionmentioning
confidence: 91%
“…The aza-Kulinkovich–de Meijere cyclopropanation of N- Boc-3-pyrroline ( 20 ) in particular had been described previously, with a reported 98:2 diastereoselectivity for the exo isomer in 76–90% yield . Reaction with N , N -dibenzylformamide ( 19 ) allows for orthogonal deprotection via hydrogenolysis to provide our desired 3- N- Boc- exo -6-amino-3-azabicyclo­[3.1.0]­hexane ( 5 ).…”
Section: Results and Discussionmentioning
confidence: 91%
“…Casey and Strotman showed that Lewis acid-mediated cyclopropanation of alkyltitanium species possessing a γ-oxo group, generated as an intermediate in the Kulinkovich hydroxycyclopropanation, , occurs with retention of configuration at Cα, consistent with a front-side mechanism for ring closure. Interestingly, the corresponding cyclopropanation of alkyltitanium species possessing a γ-iminium group generated as intermediates in the de Meijere cyclopropylamine synthesis , occurs with inversion of configuration at Cα. , …”
Section: Resultsmentioning
confidence: 99%
“…In view of the versatile new general synthesis of dialkylcyclopropylamines from N ,N -dialkylcarboxamides by way of titanacyclopropane intermediates generated from Grignard reagents and XTi(OiPr) 3 (X ¼ OiPr, Me) [60,65], de Meijere et al also turned their attention to the additional synthetic potential of titanacyclopropane intermediates generated by ligand exchange (Scheme 7) applying cyclohexylmagnesium halides as Grignard reagents [61,62,73]. This approach, which was also simultaneously developed by Cha and co-workers [74][75][76], applying a number of alkenes and favoring the use of cyclopentylmagnesium halides [77], has since been established as an efficient method for the formal dialkylaminocyclopropanation not only of a whole range of mono-, but also of some disubstituted alkenes and cycloalkenes (for selected examples see Table 3).…”
Section: Cyclopropylamines From Amides Via Ligand-exchanged Titanium-mentioning
confidence: 99%
“…Aminocyclopropanation of 1-ethenylcycloalkenes 34. [73,[82][83][84][85][86][87]. For further details see Table 5.…”
Section: Cyclopropylamines From Nitrilesmentioning
confidence: 99%